Face Orientation and Motion Differently Affect the Deployment of Visual Attention in Newborns and 4-Month-Old Infants. - Eloisa Valenza; Yumiko Otsuka; Hermann Bulf; Hiroko Ichikawa; So Kanazawa; Masami K Yamaguchi (PLoS ONE, 2015)
Orienting visual attention allows us to properly select relevant visual information from a noisy environment. Despite extensive investigation of the orienting of visual attention in infancy, it is unknown whether and how stimulus characteristics modulate the deployment of attention from birth to 4 months of age, a period in which the efficiency in orienting of attention improves dramatically. The aim of the present study was to compare 4-month-old infants' and newborns' ability to orient attention from central to peripheral stimuli that have the same or different attributes. In Experiment 1, all the stimuli were dynamic and the only attribute of the central and peripheral stimuli to be manipulated was face orientation. In Experiment 2, both face orientation and motion of the central and peripheral stimuli were contrasted. The number of valid trials and saccadic latency were measured at both ages. Our results demonstrated that the deployment of attention is mainly influenced by motion at birth, while it is also influenced by face orientation at 4-month of age. These findings provide insight into the development of the orienting visual attention in the first few months of life and suggest that maturation may be not the only factor that determines the developmental change in orienting visual attention from birth to 4 months.